Crab Mentality dalam Lingkungan Sosial: Mengenali, Memahami, dan Mengubahnya - Firni Eka Desria; Ahmad Ridfah (PT PUSTAKA CENDEKIA GROUP, 2025)
Crab mentality is a destructive social behavior pattern that arises due to envy of other people's achievements, where individuals tend to belittle people who are more successful than themselves. This phenomenon can affect social relationships and personal development. This activity aims to raise awareness about crab mentality through social media-based psychoeducation, especially Instagram, by distributing educational posters. The posters consisting of five parts were distributed for one week. After distribution, respondents who liked the posts were asked to fill out a survey form to evaluate the understanding and effectiveness of the posters. A total of 113 people responded to the posters, and 50 people filled out the survey. The survey results showed that 92% of respondents felt that the posters were interesting, understandable, and 60% of respondents felt related to their personal experiences. In addition, 60% of respondents felt better able to recognize crab mentality behavior in themselves and others. These findings indicate that social media-based psychoeducation, such as Instagram, can be a means of disseminating educational information and changing social mindsets, especially in overcoming negative behaviors such as crab mentality.